What factors influence parents’ decisions to buy products for their children? An ideal packaging proposal for mini cakes enriched with sweet potato flour - FONSECA, Maria Luiza Duarte; SANTOS, Ana Flavia Campos; COSTA, Ana Flávia Dias; SILVA, Tatiane Pereira da; OLIVEIRA , Mariuze Loyanny Pereira; MACHADO , Claysse Aparecida Alves; AZEVEDO , Alcinei Místico; PAIVA , Caroline Liboreiro; LIMA, Juliana Pinto de; VIEIRA , Claudia Regina (Food Science and Technology, 2024)
The aim of this study was to develop ideal packaging for mini cakes enriched with sweet potato flour and filled with blackberry jam. The research was conducted in two stages. In the first stage, the focus group method was used with 19 parents, divided into three subgroups based on their children’s ages: 6–9, 10–12, and 13–17 years. The interviews, conducted via Google Meet, were moderated by a researcher who followed a script of questions, with all sessions recorded with participants’ consent. Based on the collected data, eight different packaging designs were created, varying in color (purple and beige), the inclusion of games (puzzles and mobile app), and additional messages (“Satiety and energy!” and “Nutritious and tasty!”). In the second stage, 48 questionnaires were developed, each presenting the packages in different orders, and these were administered to 144 consumers. The data, analyzed using choice-based conjoint analysis, suggested that the ideal packaging for the mini cakes is purple, features puzzle imagery, and includes the message “Nutritious and tasty!”